Advances in the development of antivirals for rotavirus infection - Jiang, Lin; Tang, Ao; Song, Lihua; Tong, Yigang; Fan, Huahao (Frontiers in Immunology, 2023)
Rotavirus (RV) causes 200,000 deaths per year and imposes a serious burden to public health and livestock farming worldwide. Currently, rehydration (oral and intravenous) remains the main strategy for the treatment of rotavirus gastroenteritis (RVGE), and no specific drugs are available. This review discusses the viral replication cycle in detail and outlines possible therapeutic approaches including immunotherapy, probiotic-assisted therapy, anti-enteric secretory drugs, Chinese medicine, and natural compounds. We present the latest advances in the field of rotavirus antivirals and highlights the potential use of Chinese medicine and natural compounds as therapeutic agents. This review provides an important reference for rotavirus prevention and treatment.